2007
DOI: 10.1159/000105460
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Heterogeneity among Patients with Obesity Hypoventilation Syndrome: Therapeutic Implications

Abstract: Background: Obesity hypoventilation syndrome (OHS) can be treated with noninvasive positive pressure ventilation (NIPPV). Once clinical stability is achieved, continuous positive airway pressure (CPAP) can be recommended in many cases. However, some patients respond only partially to CPAP and NIPPV is a better option for them. Objectives: To assess treatment effectiveness in 2 groups of patients: those who could be switched to CPAP after polysomnographic titration and those who required NIPPV. Methods: A prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 44 publications
1
48
0
3
Order By: Relevance
“…Previous studies have reported improvements in clinical and biochemical endpoints in patients with obesity hypoventilation syndrome (OHS). [12,13] Although we were unable to further evaluate our patients to document the coexistence of OHS, this area warrants further study.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported improvements in clinical and biochemical endpoints in patients with obesity hypoventilation syndrome (OHS). [12,13] Although we were unable to further evaluate our patients to document the coexistence of OHS, this area warrants further study.…”
Section: Discussionmentioning
confidence: 93%
“…Patients may demonstrate a spectrum of findings: episodes of obstruction, hypoventilation or sustained obstructive hypoventilation due to partial upper airway obstruction [81]. We do not know why some obese patients develop OHS, while others do not, nor do we fully understand the pathogenesis of OHS, although it is almost certainly multifactorial in nature [82]. Some authors suggest that OHS is a mixed disorder of ‘can’t breathe’ (unable to overcome impediments to breathing resulting from derangements in lung function or the performance of the respiratory muscles) and ‘won’t breathe’ (decreased ventilatory drive disorder) [83,84,85].…”
Section: Obesity Hypoventilation Syndromementioning
confidence: 99%
“…Some authors suggest that OHS is a mixed disorder of ‘can’t breathe’ (unable to overcome impediments to breathing resulting from derangements in lung function or the performance of the respiratory muscles) and ‘won’t breathe’ (decreased ventilatory drive disorder) [83,84,85]. Ventilatory muscle dysfunction, abnormal load responsiveness, increased respiratory work and CO 2 production, impaired central respiratory drive and repeated airway occlusion during sleep are all possible pathophysiological components in this entitity, but the precise contribution of each remains to be fully clarified [81, 82, 86, 87]. Different responses to CPAP or non-invasive positive pressure ventilation (NIPPV) might reflect an intriguing possibility: the weight of the different pathophysiological mechanisms may vary in individuals with OHS.…”
Section: Obesity Hypoventilation Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Arter kan gazında solunumsal asidoza bağlı HCO 3 düzeyinde yükselme sıktır. Yapılan çalışmalarda OUAS tanısı alan hastaların kan gazlarında serum bikarbonat seviyesinin 27 mEq/L üstünde olmasının OHS için duyarlılığı %92, özgüllüğü %50 saptanmıştır (24). Polisomnografide en belirgin bulgu ciddi uzun süreli desatürasyonlardır.…”
Section: Ohs Tanısında Yardımcı Testlerunclassified